Descriptive epidemiology of scrub typhus in Nepal, 2017. (2017)
SUMMARY: Scrub typhus is a mite borne acute febrile infectious illness that is caused by Orientia tsutsugamushi. Very few attempts were made in Nepal before 2014 to investigate the presence of this disease. A total of 101 confirmed scrub typhus cases were reported from 16 districts in 2015. The magntitude of the outbreak was so disastrous in 2016 that by the end of third week of December, 831 cases of scrub typhus was reported in 47 of the 75 districts and fatalties reaching to 14. A national wide epidemiological study was thus felt necessary to understand the distribution of the disease. This study in addition documents entomological and rodentological evidence to confirm the presence of the outbreak. Line listing data of scrub typhus cases reported to EDCD were compiled and used for analysis. Data was collected from January to October 2016. Chitwan district was selected for rodentological and entomological study based on the severity and prevalence of the disease. Rodents were trapped; mites collected and laboratatory investigation of rodents and chiggers was done to confirm the presence of Orientia tsutsugamushi. Human blood samples were also collected from suspected scrub typhus patients and both IgM Elisa and IFA, the gold standard assay was done to confirm the presence of the parasite. Although 831 cases were reported in the country during April-December 2016 in Nepal, complete line listing was available for only 401 cases. Around sixty percent (59.4%) of the cases were female while the median age of the cases was 25 years. Majority of the cases belonged to Janajati/Aadhibasi (44.4%) and Brahmin/Chhetri (44.1%) ethnic groups. From Tarai 81.5% of the cases were reported while on the regional basis, the central region (45.6%) had the highest number of reported cases. Chitwan was the most affected district contributing to 34.4% of the total cases. The outbreak peaked during the month of August and September. Out of 12 rodents trapped, three were positive for chigger mites. Representative human serum samples tested by IFA confirmed the presence of Orientia tsutsugamushi in Nepal. Out of the 61 samples, 29 cases were confirmed scrub typhus positive by IFA. Similalry, two out of nine rodent serum samples were confirmed scrub typhus positive by IFA. One of the three chiggers' samples was also confirmed positive by PCR. Thus, there is clear evidence of circulation of Orientia tsutsugamushi in Nepal. The study hints the potential of scrub typhus outbreak in Nepal and there is a clear need of early preparedness and control measures.